2014
DOI: 10.1002/cne.23468
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal expression and localization of matrix metalloproteinases‐2 and ‐9 during establishment of rat hippocampal synaptic circuitry

Abstract: Matrix metalloproteinases (MMPs) are extracellular proteolytic enzymes that contribute to pericellular remodeling in a variety of tissues, including brain, where they function in adult hippocampal synaptic structural and functional plasticity. Synaptic plasticity and remodeling are also important for development of connectivity, but it is unclear whether MMPs—particularly MMP-2 and -9, the major MMPs operative in brain—contribute at these stages. Here, we use a combination of biochemical and anatomical methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 80 publications
1
37
0
1
Order By: Relevance
“…MMP-9 expression is highest during the period of cell death (first postnatal week) and declines thereafter (Murase & McKay, 2012; Aujla & Huntley, 2014). Critical survival signals for hippocampal neurons during early neonatal development include the cell adhesion molecule integrin β1, which is required for sustained activation of the serine/threonine kinase, Akt (Murase et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 expression is highest during the period of cell death (first postnatal week) and declines thereafter (Murase & McKay, 2012; Aujla & Huntley, 2014). Critical survival signals for hippocampal neurons during early neonatal development include the cell adhesion molecule integrin β1, which is required for sustained activation of the serine/threonine kinase, Akt (Murase et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Aujla and Huntley () investigated the hippocampus and found that levels of MMP‐9 transcripts peaked in all hippocampal subfields by PND4 and then declined to adult levels by PND12. The genetic deletion of MMP‐9 was shown to accelerate dendritic spine maturation, showing an early increase in the number of mature mushroom‐shaped spines on PND8.…”
Section: Expression In the Brain And Physiological Rolesmentioning
confidence: 99%
“…Laminin can be targeted and proteolytically cleaved to regulate neuronal function by active matrix metalloproteinases (MMPs), which widely exist in the early developmental period. [25][26][27] A previous study demonstrated that MMP9 can regulate neuronal survival by degrading laminin and modulating the laminin-integrin β1 signaling pathway. 16,28 Moreover, as a zinc-dependent endopeptidase, the activity of MMP9 is closely related to the concentration of free zinc ions.…”
Section: Introductionmentioning
confidence: 99%